ESTABLISHING A SYSTEM OF INDICATORS TO ASSESS THE EFFICIENCY OF USE OF BUDGETARY FUNDS - E. A. Fedchenko (Финансы: теория и практика, 2017)
Concepts of effective use of budget funds as well as budgetary sources, assessment methods and indicators hold special meaning in such scientific areas as accounting, analysis and control. Despite the fact that the effectivenessrefers to the target characteristics of the economic entity and many researchers are involved in its assessment, its definition is still unclear. The point is that these concepts are closely linked to politics and specific managementmethods at the macro level. Also, these concepts are connected with organizational and legal forms of governance and economic activities at the micro level.The article suggests the author’s definition of the term «budgetary efficiency» which takes into account the specificsof the budget process; it establishes a system of indicators to measure the efficiency of budgetary funds use and shows the relationship between three components determining the efficiency of budget spending.